Sustainable Artificial Intelligence (AI): Challenges Confronted - Saxena, Archana B; Sharma, Deepti; Aggarwal, Deepshikha (Science and Technology: Developments and Applications Vol. 5, 2025)
Artificial Intelligence has seamlessly changed our daily practices through automated techniques, robotics support, advanced Machine Learning algorithms, Expert systems and many more supporting tools. The influence and augmentation of technology have streaked out manual processing scope and opportunities. The influence and practice of AI in various domains Like Education, medicine, transport, and industry is quite apparent and bothering as well. Experts are now unfolding and exploring the “man vs machine“ aspect and are trying to sightsee the other side of this emergence. This manuscript is also working in the same aspect and particularly concentrating on areas where AI is a challenge to sustainability. Through the study, authors are trying to create thoughtfulness in various sustainability aspects by identifying the sectors where AI adoption is leaving harmful footprints for the environment and other aspects of humanity.